Integration of internet-based teaching- and learning-systems into teachership studies in sport - Thienes, G.; Weigelt, S.; Starischka, S. (International Journal of Computer Science in Sport, 2003)
Virtual university is not expected to become reality very soon. Hypermedial teaching offers likely will complete and accompany traditional teaching step by step. At present, internet-based learning- and teaching-modules are produced in the project "eBuT" (e-learning in Movement- and Training-Science) by cooperation of several universities. During the development of these multimediaconcept, among other things, the assumptions, and expectations of the target group, students in sport science, in and the using of the world-wide-web are continously evaluated. Therefore one hundret students were interrogated by questionnaire. Aside the general data exploitation, gender differences were brougth into focus and analysiszed regarding separately for the grouping of basicstudy students and main-study ones. Data show several differences between students in basic- and such in main-studies. In contrast to that no gender-specific estimations, expectations and using of the world-wide-web for participants of sport studies were found. The findings of this study point to an increasing relevance of internet-based teaching and learning in sport science. However traditional teaching should be extended and completed and not replaced by multimedia-offers forthcoming.